Rapidly evolving episodic outflow in IRAS 18113−2503: clues to the ejection mechanism of the fastest water fountain. (21st September 2018) - Orosz, G; Gómez, J F; Imai, H; Tafoya, D; Torrelles, J M; Burns, R A; Frau, P; Guerrero, M A; Miranda, L F; Perez-Torres, M A; Ramos-Larios, G; Rizzo, J R; et al.
ABSTRACT: Water fountains are evolved stars showing early stages of collimated mass-loss during transition from the asymptotic giant branch, providing valuable insight into the formation of asymmetric planetary nebulae. We report the results of multi-epoch VLBI observations, which determine the spatial and three-dimensional kinematic structure of H2 O masers associated with the water fountain IRAS 18113−2503. The masers trace three pairs of high-velocity (∼150–300 km s −1 ) bipolar bow shocks on a scale of 0${^{′′}_{.}}$ 18 (∼2000 au). The expansion velocities of the bow shocks exhibit an exponential decrease as a function of distance from the central star, which can be explained by an episodic, jet-driven outflow decelerating due to drag forces in a circumstellar envelope. Using our model, we estimate an initial ejection velocity ∼840 km s −1, a period for the ejections ∼10 yr, with the youngest being ∼12 yr old, and an average envelope density within the H2 O maser region $n_{\text{H}_2}{≈ }10^{6}$ cm −3 . We hypothesize that IRAS 18113−2503 hosts a binary central star with a separation of ∼10 au, revealing novel clues about the launching mechanisms of high-velocity collimated outflows in water fountains.